2020
DOI: 10.1177/0268355520909066
|View full text |Cite
|
Sign up to set email alerts
|

Risks and contraindications of medical compression treatment – A critical reappraisal. An international consensus statement

Abstract: Objectives Medical compression therapy is used for non-invasive treatment of venous and lymphatic diseases. Medical compression therapy-associated adverse events and contraindications have been reported, although some contraindications are theoretically based. This consensus statement provides recommendations on medical compression therapy risks and contraindications. Methods A systematic literature search of medical compression therapy publications reporting adverse events up until November 2017 was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 73 publications
(100 reference statements)
0
55
0
6
Order By: Relevance
“…The proportion of clinical nurses and outpatient care nurses within each group corresponded to the ratio of nurses in the total sample. At the beginning, all participants (case and control group) participated in a training course, in which they were taught theoretical basics of compression bandaging according to guidelines and international literature 6,7,20‐22 . Finally, all participants received a handout with the contents of the training.…”
Section: Methods and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of clinical nurses and outpatient care nurses within each group corresponded to the ratio of nurses in the total sample. At the beginning, all participants (case and control group) participated in a training course, in which they were taught theoretical basics of compression bandaging according to guidelines and international literature 6,7,20‐22 . Finally, all participants received a handout with the contents of the training.…”
Section: Methods and Participantsmentioning
confidence: 99%
“…The participants were taught the following essential basics of compression bandaging for PCB 6,7,20‐23 : A tubular cotton bandage is tightened with 2.5 times the length of the lower leg down to below the knee to protect the skin. Then an underpadding is applied to avoid pressure marks, especially of the ankle region, tibial crest and fibula head. Padding and pelottes can additionally increase the effectiveness. The enclosed metal bandage stretch clips should not be used because of the risk of injury. Adhesive fixation strips are used to fix the ending of the PCB. The bandage width should be selected according to the shape and diameter of the leg. At least two (or more depending on the leg circumference and length) bandages are required to create a PCB. The heel should always be included to avoid injuries and oedema. During the bandaging, the foot is in dorsiflexion.…”
Section: Methods and Participantsmentioning
confidence: 99%
“…1 The aim of our consensus paper was to review the available literature, to undertake a critical appraisal of reported side effects, and to provide recommendations on contraindications and risks of MC treatment. 2 The literature review was mainly based on papers listed in PubMed. Unfortunately there are only very few published studies focusing on side effects of compression.…”
Section: Dear Editormentioning
confidence: 99%
“…These complications are considered to be caused mainly by improper fitting and/or application technique. 5 ) However, this may not be simply because of the lack of experience of nurses and/or patients themselves. Postoperative leg sizes in the patients who have undergone vascular or orthopedic surgery can vary greatly depending on the severity of postoperative inflammation and/or edema.…”
Section: Introductionmentioning
confidence: 99%